KERJASAMA JERMAN DAN INDONESIA DALAM HAL PEMBELIAN SENJATA MILITER UNTUK MODERNISASI ALUTSISTA TNI - Bayu Setya Setya; Indra Pahlawan, (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research discussed about the bilateral cooperation conducted by Indonesia and Germany in terms of military weapons purchases, the Indonesian government policy related to modernize the military defense equipment set out in the policy minimum essential force or minimum essential force (MEF) in 2012. Cooperation made a major impact on changes in military power possessed by the armed forces of the Republic of Indonesia, mainly on the strength of the military land defense equipment dimensions. The theory used to analyze cooperation weapons purchases carried out by the Indonesian military of Germany is a theory of national interest by Daniel S. Papp and the theory of international cooperation by Kalevi Jaakko Holsti. From this research it can be seen, Indonesia chose Germany as a partner in the purchase of military weapons is because Germany is a strategic partner for Indonesia, it can be seen from the various agreements of cooperation in the key areas of development that have been agreed by Indonesia and Germany.Keywords: Military, Main Military Weapon, Modernization, International Cooperation